Relationships between postural balance, aiming technique and performance in elite rifle shooters - Lang, D.; Zhou, A. (European Journal of Sport Science, 2022)
The aim of the present study was to examine the relationships between postural balance, aiming technique and shooting score among elite rifle shooters at an intra- and inter-individual level. Twelve elite athletes belonging to China national team performed 60 shots under test conditions. Shooting score was used to indicate performance and footscan1.0 force platform was used to measure postural balance variables, while a SCATT MX-02 optoelectronic training device was used to measure aiming technique parameters. Inter-individual analyses indicated that postural balance was negatively correlated with shooting score (r = -0.697, P < 0.05) and aiming accuracy (r = -0.810, P < 0.01). Postural balance showed a positive correlation with the stability of hold (r = 0.923, P < 0.01) and stability of triggering (r = 0.564, P < 0.05). Intra-individual analyses indicated that there was a significant correlation between postural balance and performance, aiming accuracy and stability of hold for all shooters. Postural balance was related to the stability of triggering for six shooters. Postural balance was not statistically significant with aiming time on an intra- and inter-individual basis (P > 0.05). Our data indicated that postural balance was very important in aiming technique and shooting performance among elite rifle shooters. Additional balance programmes should be encouraged to improve a shooter`s postural balance.